Pengaruh Sistem Informasi Akuntansi Manajemen, Ketidakpastian Lingkungan, Human CapitalTerhadap Kinerja Manajerial Pada PT Bosowa Berlian Motor Makassar - M, Rahmi (STIEM BONGAYA, 2019)
This Research aims to : (1) analyze the effect Of Management accounting information systems for thePerformance manajerial PT Bosowa Berlian Motor Makassar. (2) analyze the effect environmentaluncertainty for the Performance manajerial PT Bosowa Berlian Motor Makassar. (3) analyze theeffect for Human capital for the Performance manajerial PT Bosowa Berlian Motor Makassar.Theresult of research indicate that variable of : (1) Management accounting information systems have apositive and significant influence on employee Performance manajerial PT Bosowa Berlian MotorMakassar. (2) Environmental uncertainty have a positive and significant influence on employeeperformance manajerial PT Bosowa Berlian Motor Makassar. (3) Human capital have an positive andsignificant effect on to performance manajerial PT Bosowa Berlian Motor Makassar.